DETERMINATION OF VITAMIN C IN SPINACH (Amaranthus sp.) USING TITRATION METHOD - Allefeti Sandrika; Muhammad Abdurrahman Munir; Veriani Aprilia; Emelda Emelda (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
Vitamin C is a compound that is included in the group of water-soluble vitamins. The human body really needs vitamin C intake because it can act as an antioxidant which is closely related to collagen formation and iron absorption. Vitamin C is an organic compound that the human body needs in small amounts to maintain the body metabolic functions. Vitamin C is also one of the most important vitamins in increasing the body immunity This compound is very easy to find in fruits and vegetables, one of which is spinach. Spinach is a vegetable which generally contain vitamin C with an average of 158.54 mg/100 g. The research aims to analyze vitamin C levels in spinach using a titration method or also known as iodometric titration. This research method is included in an experimental study. The sample used in this research was obtained from Kotagede Market, Yogyakarta. The titration results for each spinach will be analyzed using Microsoft Excel, where the results have shown that the levels of vitamin C contained in snapper spinach (18.95 mg/100 g), picked spinach (46.39 mg/100 g), thorn spinach (14.52 mg /100 g) and red spinach (15.42 mg/100 g). Therefore, it can be concluded that this titration method can be used to accurately measure the vitamin C content in spinach. The iodometric titration method was chosen to analyze vitamin C levels because this application is very simple when compared to other methods. Ascorbic acid or vitamin C is known as a strong reducing agent and can simply be titrated using iodine solution.